Unavoidable Practices for Effective Business Correspondence Teaching (International Journal of Scientific Research and Management (IJSRM), 2023)
As a teacher of English as a Foreign Language in general and (the teacher) of English business correspondence in particular in Mbujimayi, I noticed fifth and six-year pupils’ weakness in business letter writing. Looking for weakness causes and how to achieve success, I have written this paper in order to make suggestions. Questionnaire and classroom observation have helped me to collect the data. The analytical and comparative methods have been used to find out whether what teachers do in class aligns with what is advocated by experts in the field. The study has revealed that 60% of the teachers said that the textbooks they use does not match with the criteria of contents and teaching approach while 40 % said the textbooks do. 80% of the teachers use samples of letters for reading activities while 20% said they do not. 80% of the teachers said pupils usually write letters at home but sometimes in class while 20% said their pupils usually write letters at home but sometimes at home. 100% of the teachers teach business correspondence as a theory course, not like a practical writing class. 100% of the teachers said pupils have vocabulary problems. In terms of suggestions to remedy this situation, the following unavoidable practices can help to achieve learner success in this field: (1) Learners’ Needs Analysis, Material Adaptation and Simulation, (2) Learner-centeredness in English Commercial Correspondence Teaching, (3) Vocabulary and Reading prior to Letter Writing, (4) Repetitive Pupils’ Work under the Teacher’s Supervision.